ANALISIS IMPLEMENTASI KEBIJAKAN IZIN LOKASI DALAM PEMBANGUNAN KAWASAN EKONOMI KHUSUS (KEK) KOTA PALU - Maisura, Amanda; Tjaija, Abu; Pasinringi, Andi (Katalogis, 2019)
Based on the Analysis of the Implementation Policy of the Location Permit for the Construction of the Special Economic Zone of the City of Palu by using a theory built by Edward III, with four 4 dimensions namely: Communication, resources, disposition, and biocratic structure, it can be concluded, that the implementation of the policy shows results that well, because four 4 dimensions have been fulfilled with the resulting performance is 65% on average, since the special economic zone was established in 2016-2021, and there are only three years left in the Palu Economic Special Zone Administrator Strategic Plan. it means that the performance of the Administrator of the Special Economic Zone of the City of Palu is very optimistic in achieving the Strategic Plan target in 2021. It is recommended that, the Administrator of the Palu Special Economic Zone, need to take strategic steps; such as having sufficient funds to make land acquisition, minimizing brokers as third parties in land acquisition, and having to set low tarif standards and the highest tarifs on permeter land prices, through regional regulations.